Norway : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
The current slowdown in the Norwegian economy has followed an exceptionally prolonged phase of expansion. The current slowdown in economic growth is expected to continue. Over the longer term, the public finances face challenges as oil revenues begin to run out and pension liabilities escalate. Support to agriculture deserves high priority. There is scope to improve the performance of the labor market by liberalizing regulations and allowing for greater wage differentiation. The privatization initiatives should be pursued vigorously to improve efficiency and corporate governance.